Haematological Assessment of Methanolic Stem Extract of Cissus quadrangularisLinn. against Freund’s Complete Adjuvant induced Female Albino Arthritic Rats: Life Sciences-Biochemistry for Better Diagnosis and Therapy - S. Shamina; Anjana; S. Suja (International Journal of Life Science and Pharma Research, 2022)
Rheumatoid arthritis is a chronic, inflammatory and autoimmune disorder. Rheumatoid arthritis is a joint destruction which occurs due to increased expression of cytokines and transcription factors. Cissus quadrangularis belongs to the Vitaceae family. The plant shows anti-osteoporotic, anti-inflammatory and anti-microbial properties. Soxhlet method was used for the extraction of the plant using methanol as a solvent. The anti-arthritic activity of methanolic extract of Cissus quadrangularis was evaluated by in vivo study. The present study assess the haematological parameters in female albino rats after the induction of Freund’s Complete Adjuvant. Dexamethasone was used as the standard reference drug. The study showed varied changes in the haematology after the arthritic induction by 0.1 ml FCA which were analyzed before and afterthe treatment period. The inhibition of secondary inflammation in adjuvant arthritic rats by methanolic extract of Cissus quadrangularis was studied by haematological parameters. The total haemoglobin, total RBC, total WBC, ESR and RF values were assessed before initiation of the treatment and after for 28 days of the treatment. The results showed significant incline or decline in each parameter in the study period of 28 days. While their changes were rectified with the oral administration of methanolic extract of the plant at a dose of 250mg/kg. The methanolic extract boosted the levels of Hb, RBC and simultaneously reduced WBC, ESR levels along with the serological factor RF. The plant extract showed effective results in the haematological parameters, when compared to the standard reference drug Dexamethasone. The results from the study suggest that the plant has potential effect in curing arthritis.